Overqualification and Subjective Well-Being at Work: The Moderating Role of Job Autonomy and Culture - Wu, C.; Luksyte, A.; Parker, Sharon (Springer Netherlands, 2015)
Overqualification is a form of underemployment wherein people have more skills, experience, knowledge, and abilities than required for a job. Past research has shown that overqualification is negatively related to subjective well-being at work, such as lower job satisfaction. To mitigate this negative impact, drawing on a job design perspective, the authors proposed that job autonomy can buffer overqualification’s negative effects. Based on the model of culture fit in managerial practice, as well as regulatory fit theory, the authors further proposed that the buffering effects of job autonomy apply only to employees from individualistic (vs. collectivistic) cultures. Data from the 5th European Working Conditions Survey were analyzed. Results of a two-level multilevel modeling analysis showed a three way interaction between overqualification, job autonomy, and national culture in predicting subjective well-being at work. Job autonomy buffered the negative effects of overqualification on subjective well-being at work, but only in individualistic cultures.